Perbedaan Skor Functional Independence Measure (FIM) pada Pasien Rawat Inap dengan Stroke Iskemik dan Stroke Hemoragik di Rumah Sakit di Kota Bengkulu Tahun 2018 - Nugraha, Panji Harry Priya; Bantolo, Suryo; Kurniati, Annelin; Erlinawati, Noor Diah; Nasution, Ahmad Azmi (Sriwijaya Journal of Medicine, 2018)
Stroke is one of the most common causes of disability in the world. Patients with ischemic stroke have different functional improvements from patients with hemorrhagic stroke. The tool is the Functional Independence Measure (FIM) questionnaire. This study aims to determine the difference in FIM scores in hospitalized patients with ischemic stroke and hemorrhagic stroke at hospitals in Bengkulu City. This research is an observational analytic research with cross-sectional design. The study involved stroke patients who hospitalized at RS Bhayangkara Bengkulu City, RSUD Bengkulu City, and RSUD dr. M. Yunus Bengkulu City from January-April 2018 with total sample 22 ischemic stroke patients and 22 hemorrhagic stroke patients who met the inclusion criteria. FIM scores as independent variables, while the type of stroke as dependent variables. The difference between the two variables was analyzed by unpaired t test and Mann-Whitney test. Patients with ischemic stroke had admission FIM score higher than patients with hemorrhagic stroke (26 vs 13,5; p=0.006). There were no differences in discharge FIM score in patients in both types of stroke (1,67 vs 1,58; p=0,081). There was no difference in FIM score gain between patients with ischemic stroke and patients with hemorrhagic stroke (4,12 vs 4,36; p=0,444). Patients with ischemic stroke had higher admission FIM score compared to patients with hemorrhagic stroke, but there was no significant difference in FIM score gain during hospitalization between ischemic stroke and hemorrhagic stroke patients at hospitals in Bengkulu City.